Supervisory and Preventive Functions of the Federal Assay Chamber ("Journal "U". Economy. Management. Finance.", 2026)
The Federal Assay Chamber ensures control and supervision in the sphere of circulation of precious metals and gemstones, playing an important role in maintaining market transparency and legality. The annotation highlights key areas of oversight, including hallmarking, financial monitoring, and licensing, as well as the significance of the risk-oriented approach. Special attention is given to preventive measures aimed at reducing violations and strengthening the integrity of market participants.
Keywords: assay supervision; risk-oriented approach; preventive measures